Financial analysis and financial plan of Thyssenkrupp AG - Markova, Sofiia (2025)
The financial analysis of Thyssenkrupp AG, a German industrial conglomerate, over the past six years of its performance.The theoretical and empirical parts focused on Financial Ratio Indicators, Vertical and Horizontal analyses, and a comparison with its Peer Group.Background of the strategic decisions: the scheduled separation of Thyssenkrupp Marine Systems and the segment‘s dissolution of Elevator Technology.Interpretation of the results for stock advice with a financial plan for 2025.